2016
DOI: 10.1136/svn-2016-000018
|View full text |Cite
|
Sign up to set email alerts
|

High HbA1c is associated with higher risk of ischaemic stroke in Pakistani population without diabetes

Abstract: ContextThe role of glycated haemoglobin (HbA1c) in the prediction of ischaemic stroke in individuals without diabetes is underestimated.AimsWe performed a study to analyse the role of HbA1c in the risk prediction of ischaemic stroke in Pakistani population without diabetes. We further studied the difference between HbA1c values of individuals with diabetes and without diabetes with stroke.Settings and designSingle centre, case–control.Materials and methodsIn phase I, a total of 233 patients without diabetes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The mean age ± SD in present study was 60.86 ± 12.51 years compared to study done by Vaidya C et al [10] and Maskey A et al [11] where it was 61 and 63 year respectively. The major age group was >70 year followed by 61-70 years compared to study done by Vaidya C et al [10] and similar study by Ukoha OB et al [12] Mean age ± SD in diabetic group was 59.25 ± 11.13 years compared to 55.6 years in study done by Nomani AZ et al [13] Mean age ± SD was 62.03 ± 13.30 years in nondiabetic group compared to study done by Nomani AZ et al [13] The major age group in diabetic group was 51-60 compared to >70 years in non-diabetic group. In this study age was found to be an important factor for ischemic stroke similar to what was concluded from Helsinki Young Stroke Registry which finds the frequency of ischemic stroke rises sharply beginning at the age of 40.…”
Section: Age Wise Distribution Of Stroke Patientsmentioning
confidence: 58%
See 1 more Smart Citation
“…The mean age ± SD in present study was 60.86 ± 12.51 years compared to study done by Vaidya C et al [10] and Maskey A et al [11] where it was 61 and 63 year respectively. The major age group was >70 year followed by 61-70 years compared to study done by Vaidya C et al [10] and similar study by Ukoha OB et al [12] Mean age ± SD in diabetic group was 59.25 ± 11.13 years compared to 55.6 years in study done by Nomani AZ et al [13] Mean age ± SD was 62.03 ± 13.30 years in nondiabetic group compared to study done by Nomani AZ et al [13] The major age group in diabetic group was 51-60 compared to >70 years in non-diabetic group. In this study age was found to be an important factor for ischemic stroke similar to what was concluded from Helsinki Young Stroke Registry which finds the frequency of ischemic stroke rises sharply beginning at the age of 40.…”
Section: Age Wise Distribution Of Stroke Patientsmentioning
confidence: 58%
“…The Atherosclerosis Risk in Communities (ARIC) Study [22] found that in diabetic group patients the adjusted risk of stroke was 2.33 (95% CI 1.29-4.21) in highest percentile of HbA1c (>6.8%) as compared with the lowest one (<4.7%), Nomani AZ et al [13] mean HbA1c values were significantly higher in the diabetes group (7.6 ± 2.1 vs 6.1 ± 2.3) (p<0.05).…”
Section: Hba1c and Duration Of Diabetesmentioning
confidence: 99%
“…Higher HbA1C levels correlated with a higher clinical risk, even in nondiabetic patients. An increased risk of ischemic stroke has been reported when HbA1c levels exceed 5.6% 15,16) . A meta-analysis including 36 observational cohort and nested case-control cohort studies showed a 49% increase in the risk of first-ever ischemic stroke for every 1% increase in the HbA1c level in non-diabetic cohorts 17) , suggesting that maintaining lower HbA1c levels protects patients from adverse CV events.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, women were reported to have more aphasia, dysphagia and visual field disorders than men, while no differences were reported for motor and sensory deficits. [5][6][7][8] From the demographic data obtained hemorrhagic stroke patients with an average age of 52.19±14.12 years whereas in ischemic stroke patients the mean age was 52.71±10.88 years, according to Bushnell et al that stroke patients female sex live longer, and risk Lifelong strokes at the age of 55-75 years are higher in women than men. 9 From the demographic data in this study obtained ischemic stroke patients and acute hemorrhagic stroke with a level of education that is more high school, where in the study of Samal et al, which states the role of education is needed to reduce the occurrence of risk factors for stroke by 40%.…”
Section: Discussionmentioning
confidence: 99%